Rancang Bangun dan Evaluasi Kinerja Kotak Pendingin Berbasis Termoelektrik - Tajri Maulana; Teuku Azuar Rizal; Nazaruddin (Fakultas Teknik Universitas Samudra, 2021)
The cooler is one of the necessities for humans to store food, drinks, vegetables, fruit, meat and so on. Refrigeration systems that are commonly used today use refrigerants or freon/CFC (Chlor Fluoro Carbon) which are less environmentally friendly and expensive. To meet the need for cheap and environmentally friendly refrigerators, an alternative cooler is needed. One alternative refrigerant that has been widely used today is thermoelectric. The power source is from an adapter with an output voltage of 12V – 36V DC6A. Peltier Is a Thermo-Electric Module. This component is coated by a thin ceramic that contains Bismuth Telluride rods in it. When the DC supply voltage is 12volt-15volt and current is 2-5A. The cooling room material is Styrofoam, with a heat sink in the form of a heat sink fan. Variations are made on the amount of thermoelectric used. Data retrieval is done by installing a voltmeter, ammeter and thermocouple in a predetermined position then each measuring instrument will display the data. The data is then processed using the Microsoft Excel program which can produce graphs. With a graphic form, discussion and conclusion can be done easily.